The UK Ministry of Defence Project Orientated Environmental Management System (POEMS) - Galante, Erick; Temple, Tracey; Ladyman, Melissa K.; Gill, Philip P. (Wiley, 2017)
The Project Orientated Environmental Management System (POEMS) is the UK Ministry of Defence (MoD) bespoke environmental management system for the acquisition and use of equipment. The full implementation of a site-specific environmental management system is challenging for the MoD because there are many permanent MoD sites with transient populations, frequently changing site activities and diverse types of equipment. Nevertheless, MoD policy requires that all sites are covered by an environmental management system. POEMS is based on international standards ISO14001 and ISO14040, which focus on environmental management systems and life cycle assessment, respectively. The primary aim of POEMS is to identify and manage any environmental aspects (causes) and impacts (effects) by scrutinising MoD equipment and activities during acquisition, operation and disposal. This is achieved by drawing up a priority list of activities associated with the equipment based on anticipated environmental impact scores, resulting in an environmental management plan that spans the life cycle of the equipment and any corresponding activities. This article describes the POEMS procedure for both experts and non-experts, and demonstrates the implementation of POEMS using a 105-mm artillery round as a theoretical case study. The results anticipated at each stage of the POEMS procedure are discussed in detail, and the documentation necessary to verify the correct application of POEMS is demonstrated.
Special Issue: Energetic Materials and the Environment
Keywords: POEMS; Environmental Management Systems; Life Cycle Assessment; International Organization for Standardization; UK Ministry of Defence